A Comparative Study of CoNi-LDH/ZnO Film for Photocathodic Protection Applications in the Marine Environment - Zhang, Xuan; Wang, Yanhua; Zhang, Dongmei; Tao, Zhencheng (Frontiers in Materials, 2022)
In this study, two kinds of Co–Ni-layer double hydroxide (LDH)/ZnO films were prepared with different morphologies by a simple electrochemical method. The properties of the films were investigated by SEM, XRD, UV–Vis DRS, XPS, and electrochemical techniques. It was found that Co–Ni-LDH-modified ZnO films exhibited excellent photocathodic properties in a scavenger-free environment. This is mainly due to the absorption of visible light by LDH, the formation of p–n heterojunction, and the depletion of photo-generated holes by the cycling process of Co (II)/Co (III). Compared with CoNi-LDH/ZnO nanorods, CoNi-LDH/ZnO nanoclusters showed better photocathodic protection performance and physical barrier effect. Under illumination conditions, the rough surface of ZnO nanoclusters and the deposition of a large amount of LDH can provide more photoelectrochemical active sites, thus improving the light absorption capacity and photocathodic protection performance of CoNi-LDH/ZnO nanoclusters. Under dark conditions, the physical barrier effect of CoNi-LDH/ZnO nanoclusters was also enhanced by the dense ZnO nanoclusters and thick CoNi-LDH layers.